The Australian Community Does Not Support Gender Selection by IVF for Social Reasons - Gab, Kovacs; Julian, McCrann; Michele, Levine; Gary, Morgan (International Journal of Reproductive Medicine, 2013)
This study was carried out to determine the attitudes of the Australian community to IVF by a reliable community poll. Cross-sectional surveys, conducted by telephone of a random sample of 650 Australians were undertaken. The sample was drawn from the residential phone numbers in the Australian electronic “White Pages” and stratified by geographical area with quotas controlled by gender and age to be representative of the Australian population. The participants were asked to answer to three questions about gender selection, and their response was measured as “yes-allowed,” “no-not allowed,” or “undecided” for each of the questions. Whilst 91% of respondents supported the use of IVF to help infertile couples, only 20% supported gender selection within IVF or for family balancing. When it came to the use of IVF only for gender selection, only 17% were in favour. This survey shows that Australian community overwhelmingly opposes gender selection for social reasons.